Prevalence of cervicogenic dizziness in patients with neck pain and effectiveness of cervicogenic dizziness rehabilitation (Annals of Medical Research, 2024)
Aim: This study aims to determine the frequency of cervicogenic dizziness in patients suffering from neck pain and observe the efficacy of cervicogenic dizziness (CGD) rehabilitation.Materials and Methods: It was a retrospective study. The patients aged between 18 and 65 who attended the physical medicine and rehabilitation outpatient clinic and suffered from neck pain were included in the study. Pregnant patients with a history of cervical surgery, missing data, or attending the rehabilitation program irregularly were excluded. Demographic data, treatment protocols, laboratory and radiology results, and Dizziness Handicap Inventory Scores in the 1st and 3rd month after rehabilitation were obtained from the health database. The frequency and reasons for cervicogenic dizziness and the efficacy of the rehabilitation program were observed. P < 0.05 was considered statistically significant.Results: Totally, 443 patients were analyzed. 288 patients were female, and 155 were male. The mean age was 50.31 ± 14.06. Cervical disc herniation was determined in 40% (n = 178) of the patients, cervical spondylosis was observed in 11.5% (n = 51) of patients, 45.5% (n = 202) of patients had myofascial pain syndrome and 1.5% (n = 6) of patients defined trauma. Neck pain was associated with dizziness in 8.57% (n = 38). Cervicogenic dizziness was determined in 8.1% of the patients, and the most common reasons were myofascial trigger points and cervical disc hernia. Patients who accepted the cervicogenic rehabilitation program had a better Dizziness Handicap Inventory Score in the 1st and 3 rd month controls.Conclusion: Cervicogenic dizziness was determined in 8.1% of patients suffering from neck pain. It was detected that the most common reason was cervical pathologies, and the patients benefited from rehabilitation program.
Keywords: Cervical pain; Dizziness; Myofascial trigger point; Positional vertigo